OFDM system based on framelet transform and radon mapping with FPGA implementation
Increasing demands for high speed data transmission and unrivalled spectral efficiency are drivers for the current and future wireless communication systems. Orthogonal Frequency Division Multiplexing (OFDM) has been recognized as one of the most promising techniques for supporting high data rate transmission due to its promising attributes. Nonetheless, and despite all the advantages of this technique, OFDM signal suffers from the fading implications of the wireless channels that cause even more Inter-Symbol Interference (ISI) and Inter-Carrier Interference (ICI). Therefore, Cyclic Prefix (CP) is employed in the traditional OFDM to entirely eradicate ISI/ICI, but this approach affects the transmission efficiency by losing about 25% of the available bandwidth. Therefore, a novel OFDM system based on a new combination between Framelet Transform (FT) and Finite Radon mapping (FRAT) is proposed in this thesis in order to enhance the immunity of OFDM system against the detrimental effects of multipath fading and increasing its ability to eradicate the ISI and ICI in the presence of a simple equalizer without the necessity for CP. The proposed system, called N-FRATFT- OFDM, was simulated and compared to other OFDM systems, such as FFT-based OFDM using N-FRAT mapping (N-FRAT-FFT-OFDM), FT-based OFDM using QAM mapping (QAM-FT-OFDM), and FFT-based OFDM using QAM mapping (QAM-FFTOFDM). The simulation was conducted for various constellation points over different channel conditions and parameters using MATLAB software. The results showed that the new structure outperformed the other three systems by reducing ISI/ICI, which then improved the performance of the Bit Error Rate (BER). For instance, in the frequency selective fading channel and maximum Doppler frequency (fd =100 Hz) with 4-FRAT mapping, which is equivalent to 16-QAM mapping, 4-FRAT-FT-OFDM reported 12.35 dB and 19.35 dB gain in the Energy per bit to Noise power spectral density ratio (Eb/No) measured at BER = 10-3 compared with 4-FRAT-FFT-OFDM and 16-QAMFFT- OFDM, respectively, while the 16-QAM-FT-OFDM system washout to attain such BER. Moreover, Alamouti Space-Time Block Code (STBC) was proposed in the structure of N-FRAT-FT-OFDM system to further enhance BER performance at high data rates and increase bandwidth efficiency by increasing the spatial diversity of the system. A proposed system is equipped with two different approaches of STBC: the first is STBC-based N-FRAT-FT-OFDM (STBC-N-FRAT-FT-OFDM), with two transmitter antennas and one receiver antenna (2Tx-1Rx), while the second is STBC-NFRAT- FT-OFDM, with two transmitters and two receiver antennas (2Tx-2Rx).